2016
DOI: 10.1590/1414-431x20165058
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of sex hormones does not affect 17-ß-estradiol-induced coronary vasodilation in the isolated rat heart

Abstract: The relaxation of coronary arteries by estrogens in the coronary vascular beds of naive and hypertensive rats has been well described. However, little is known about this action in gonadectomized rats. We investigated the effect of 17-ß-estradiol (E2) in coronary arteries from gonadectomized rats, as well as the contributions of endothelium-derived factors and potassium channels. Eight-week-old female and male Wistar rats weighing 220-300 g were divided into sham-operated and gonadectomized groups (n=9−12 anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Hormonal dysfunction in OVX females is an important factor to the development of hypertension and coronary artery disease because the presence of estrogen is able to modulate the NO synthesis by acting on the isoforms of the enzyme nitric oxide synthase (NOS). Indeed, results from our laboratory indicate that the main endothelial mediator responsible for regulating the coronary vascular tone (represented by the baseline CPP) is the NO in both Wistar and SHR rats (Santos et al, 2004, 2010, 2016). Therefore, ovariectomy leads to damages on the endothelial function, as previously showed by our study group (Borgo et al, 2011; Caliman et al, 2013; Claudio et al, 2013; Oliveira et al, 2014; Lamas et al, 2015); impairing thus, the preventive/therapeutic effects from the PHE on the baseline CPP values in the OVX-PHE group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hormonal dysfunction in OVX females is an important factor to the development of hypertension and coronary artery disease because the presence of estrogen is able to modulate the NO synthesis by acting on the isoforms of the enzyme nitric oxide synthase (NOS). Indeed, results from our laboratory indicate that the main endothelial mediator responsible for regulating the coronary vascular tone (represented by the baseline CPP) is the NO in both Wistar and SHR rats (Santos et al, 2004, 2010, 2016). Therefore, ovariectomy leads to damages on the endothelial function, as previously showed by our study group (Borgo et al, 2011; Caliman et al, 2013; Claudio et al, 2013; Oliveira et al, 2014; Lamas et al, 2015); impairing thus, the preventive/therapeutic effects from the PHE on the baseline CPP values in the OVX-PHE group.…”
Section: Discussionmentioning
confidence: 96%
“…Besides its scavenger effect, we have previously shown that pomegranate is able to reduce the angiotensin-converting enzyme (ACE) activity (Santos et al, 2016) contributing to an environment with less oxidative stress consequently reducing CVDs risk (Aviram and Dornfeld, 2001; Mohan et al, 2010). In addition, with the ACE inhibition there is a decreasing in bradykinin degradation that may contribute to our results (Shiuchi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(Moyses et al 2001) showed that oestrogen replacement in gonadectomized rats restores the baseline CPP in females and increases the CPP in males to become similar to those found in naive female animals. Indeed, a recent study from our group also showed that gonadectomy reduces the baseline CPP in females and has no effect on the baseline CPP of hearts from male rats (Santos et al 2016). Notably, even after gonadectomy, these differences in the CPP continued to exist between females and males, perhaps because the benefits of oestrogens on the coronary arteries were not completely lost after gonadectomy.…”
Section: Figurementioning
confidence: 76%
“…In our study, the acute administration of G-1 promoted vasodilation in the coronary vascular beds of isolated hearts from male and female rats. Our previous studies have already demonstrated that E2 is able to induce a relaxing response in the coronary vessel (Santos et al 2004(Santos et al , 2010(Santos et al , 2012(Santos et al , 2016. However, such actions could not be directly attributed to GPER, since oestradiol also acts on intracellular receptors (ERα and ERβ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation